2009
DOI: 10.1101/gr.084509.108
|View full text |Cite
|
Sign up to set email alerts
|

Into the blue: Gene duplication and loss underlie color vision adaptations in a deep-sea chimaera, the elephant sharkCallorhinchus milii

Abstract: The cartilaginous fishes reside at the base of the gnathostome lineage as the oldest extant group of jawed vertebrates. Recently, the genome of the elephant shark, Callorhinchus milii, a chimaerid holocephalan, has been sequenced and therefore becomes the first cartilaginous fish to be analyzed in this way. The chimaeras have been largely neglected and very little is known about the visual systems of these fishes. By searching the elephant shark genome, we have identified gene fragments encoding a rod visual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 76 publications
(98 reference statements)
1
89
0
Order By: Relevance
“…In EJ-LWS, these sites were occupied by AHYTA residues and the predicted λ max was 553nm, longer than our measurement. Davies et al (Davies et al, 2009;Davies et al, 2012) reported that the λ max value of elephant shark Callorhinchus milii LWS1 (EF565165) expressed in an in vitro experiment was not consistent with the 'five-site' rule, because of inactivation of the chloride ion positive charge of H197 caused by amino acid substitution of A308S. The EJ-LWS has amino acid residues H and A at sites 197 and 308 and our present knowledge could not explain the molecular mechanisms involved in the blue shift.…”
Section: Opsin Types and Visual Pigment Correspondencementioning
confidence: 40%
“…In EJ-LWS, these sites were occupied by AHYTA residues and the predicted λ max was 553nm, longer than our measurement. Davies et al (Davies et al, 2009;Davies et al, 2012) reported that the λ max value of elephant shark Callorhinchus milii LWS1 (EF565165) expressed in an in vitro experiment was not consistent with the 'five-site' rule, because of inactivation of the chloride ion positive charge of H197 caused by amino acid substitution of A308S. The EJ-LWS has amino acid residues H and A at sites 197 and 308 and our present knowledge could not explain the molecular mechanisms involved in the blue shift.…”
Section: Opsin Types and Visual Pigment Correspondencementioning
confidence: 40%
“…Therefore, it may be that at the time in evolutionary history when the jawed and jawless vertebrates split into two lineages, the eyes of lampreys possessed a predominantly photopic visual system based on cone-like photoreceptors. However, at least one type of receptor was undergoing some sort of 'transmutation' to a receptor hybrid, which would subsequently become a 'true rod' with the age of cartilaginous fishes (Walls 1942;Pisani et al 2006;Davies et al 2009). …”
Section: Evolution Of Early Photoreceptors (A) Rods or Cones?mentioning
confidence: 99%
“…In vertebrates, molecular phylogenetic analyses have established that vertebrate visual pigments evolved along five distinct lines and that these lineages may have been in place before the divergence of jawed and jawless fishes (Davies et al 2009; figure 2). The five vertebrate visual pigment gene lineages presumably diverged from a single common ancestor that had evolved prior to the divergence of the protostomes and deuterostomes, which is thought to have occurred about 700 Ma (Oota & Saitou 1999).…”
Section: Functional and Behavioural Implications For Early Photorecepmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely assumed that variations in the peak spectral sensitivities (l max ) of the visual system represent adaptations to specific visual needs associated with particular habitats or lifestyles (Lythgoe, 1979;Peichl, 2005;Davies et al, 2009). Spectral sensitivity is determined either by changes in the tertiary structure of the opsin protein via amino acid substitutions and/or by the use of alternate chromophores derived from vitamin A1 or A2 (Crescitelli et al, 1972;Yokoyama, 2000;Bowmaker and Hunt, 2006;Hart and Hunt, 2007).…”
Section: Introductionmentioning
confidence: 99%